Religious Symbols and Demythologising - Galloway, Allan D. (Scottish journal of theology, 1957)
The following is intended as a contribution to the current J. demythologising controversy. I hope it will either bring some clarification or else add profitably to the prevailing confusion.I write as a man of faith to men of faith. That is to say, I am not here concerned with whether the Christian faith is true or how much of it ‘we can accept’. That is a question which must be discussed in quite another way and in quite another context. I shall assume that we accept it in the same way as Carlyle accepted the universe, only more so, for Christ is Lord of the Universe. I am concerned rather with the way in which the symbols in which we express our belief behave.